2020
DOI: 10.4315/jfp-20-127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Activity of Buforin I and Nisin and the Synergistic Effect of Their Combination as a Novel Antimicrobial Preservative

Abstract: One of the most effective methods for increasing the antimicrobial activity of a substance is to combine it with one or more other antimicrobial agents. The aim of the present study was to evaluate the antimicrobial effect of buforin I and nisin alone and investigate the synergistic action of these compounds against the most important food spoilage microorganisms in clouding B. subtilis, S. epidermidis, L. innocua, E. coli, S. Enteritidis, A. oryzae, R. glutinis and G. candidum. The results of MIC and MBC/MFC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 71 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…Due to the increased incidence of resistance by bacteria to conventional antimicrobial drugs natural products such as propolis, antimicrobial peptides and essential oils are alternatives that aim to control bacterial growth, especially for P. alvei and others of same genus [47][48][49][50], and B. subtilis [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased incidence of resistance by bacteria to conventional antimicrobial drugs natural products such as propolis, antimicrobial peptides and essential oils are alternatives that aim to control bacterial growth, especially for P. alvei and others of same genus [47][48][49][50], and B. subtilis [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Three different temperatures were considered according to the origin of pathogens in MIC test. Accordingly, normal dairy cattle body temperature (312 K) 34 , normal avian body temperature (315 K) 33 and water boiling temperature at sea level were used.…”
Section: Methodsmentioning
confidence: 99%
“…Medium without inoculum was considered as negative control and Gentamicin (μg/mL) used as positive control 32 . After MIC test, 100 μL of dilutions with no bacterial growth pour-plated on Mueller–Hinton agar medium and incubated at 37 °C for 24 h. The MBC was determined based on the lowest bactericidal concentration showing no visible growth on culture plates 32 , 33 .…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have revealed that nisin has good antibacterial properties. Roshanak et al (2020) found that nisin can act on Bacillus subtilis, Staphylococcus epidermidis, Listeria innocua, Escherichia coli, Salmonella enteritidis, Aspergillus oryzae, Rhodotorula glutinosa, Geotrichum candidum, etc. Nisin can be used for preservation of chicken breasts and inhibit the growth of spoilage bacteria.…”
Section: Nisinmentioning
confidence: 99%